A cooperação jurídica internacional na era da tecnologia e o papel da Interpol : uma porposta a partir das novas ferramentas de investigação - Isbarrola, Alexandre da Silveira (2022)
Globalization and technological evolution have substantially modified the world, making relationships more complex, accelerating the occurrence of events and instituting a network society. In the course of these transformations, there has been an important change in the configuration of criminality, which has become increasingly sophisticated, technological and transnational, bringing unprecedented challenges in the context of criminal prosecution. These difficulties are largely due to the obsoleteness of investigative tools, designed to face an outdated paradigm of crime, which today is no longer limited to national borders. In this context, instruments of international legal cooperation become particularly relevant – which, however, have not always been sufficiently agile and resolute in the face of new demands. On the other hand, spyware programs emerge as promising tools in the field of criminal investigation, making it possible to obtain remote evidence located anywhere in the world. In view of these questions, this thesis presents a proposal for the evolution of international cooperation in criminal matters, as well as the technological tools available to investigative bodies, so that they can offer faster, more effective and coordinated responses to globalized and virtualized crime. These possibilities, however, must be considered within constitutional limits, protecting fundamental rights and guarantees, as well as the sovereignty of States.